1999
DOI: 10.2307/3870849
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Repression of Vacuolar and Cell Wall Invertase in Transgenic Carrot Alters Early Plant Development and Sucrose Partitioning

Abstract: To unravel the functions of cell wall and vacuolar invertases in carrot, we used an antisense technique to generate transgenic carrot plants with reduced enzyme activity. Phenotypic alterations appeared at very early stages of development; indeed, the morphology of cotyledon-stage embryos was markedly changed. At the stage at which control plantlets had two to three leaves and one primary root, shoots of transgenic plantlets did not separate into individual leaves but consisted of stunted, interconnected green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 17 publications
2
73
0
1
Order By: Relevance
“…Thus, the apoplastic carbohydrate supply pathway for the pollen is controlled both by the surrounding tissues of the anther and by the developing pollen in a sequential manner (21). This study strongly supports the importance of apoplastic cleavage of sucrose by extracellular invertase for supplying carbohydrates to sink tissues and for normal development of plants, which has been suggested by an increasing number of studies in recent years (42)(43)(44)(45). A number of studies have shown that cell wall invertases are sink tissue specifically expressed and up-regulated by stimuli that are associated with an increased demand for carbohydrates such as stress-related stimuli and growth-stimulating phytohormones (25).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Thus, the apoplastic carbohydrate supply pathway for the pollen is controlled both by the surrounding tissues of the anther and by the developing pollen in a sequential manner (21). This study strongly supports the importance of apoplastic cleavage of sucrose by extracellular invertase for supplying carbohydrates to sink tissues and for normal development of plants, which has been suggested by an increasing number of studies in recent years (42)(43)(44)(45). A number of studies have shown that cell wall invertases are sink tissue specifically expressed and up-regulated by stimuli that are associated with an increased demand for carbohydrates such as stress-related stimuli and growth-stimulating phytohormones (25).…”
Section: Discussionsupporting
confidence: 64%
“…It also has been shown that an arrest in pollen development in wheat because of a water deficit during meiosis correlated with alterations in carbohydrate metabolism and a drastic decrease in invertase activity (23). Antisense repression of an extracellular invertase in carrot under control of the constitutive 35S promoter strongly interferes with regeneration of the transformed plants and resulted in pleiotropic effects (43). This further supports the highly restricted expression pattern of the Nin88 promoter during anther development because we could not observe any effect during plant growth and development, and even anther formation was phenotypically normal.…”
Section: Discussionmentioning
confidence: 99%
“…Vac-Inv is important for osmotic purposes and to supply energy. In Daucus carota, antisense suppression of CWInv or Vac-Inv resulted in altered source-sink ratios and carbohydrate levels, although the effects were more pronounced in antisense CW-Inv plants (11). In tomato fruits, a QTL for total soluble solids turned out to be a CW-Inv (18).…”
Section: A Role For Vacuolar or Cell Wall Invertase In Controlling Elmentioning
confidence: 99%
“…The relative usage of Inv or Susy pathways might also be due to energetic reason, because Susy requires less ATP to breakdown sucrose as compared to Inv, in combination with hexokinase (9). When trying to establish a possible role for these enzymes in the regulation of sink activities, several problems may arise, including: (i) all plant species tested so far have multiple genes for both Susy and Inv (10)(11)(12), and it is unlikely that they are all involved in regulation of sink strength in different organs, and (ii) expression of these genes may have profound organ-specific patterns and may vary during plant and͞or organ development (5,10,12,13).…”
mentioning
confidence: 99%
“…The first enzyme yields UDP-glucose and fructose in a reversible reaction in the cytosol, whereas invertases in the cytosol, the vacuole or the cell wall release glucose and fructose in an irreversible reaction. Both types of enzymes have been shown to be essential for plants, especially during growth, storage compound accumulation, and stress responses [1,2].…”
Section: Introductionmentioning
confidence: 99%